Analisis Perilaku Aparat Desa dalam Meningkatkan Mutu Pelayanan Publik di Kantor Desa Momalia 1 Kecamatan Posigadan Kabupaten Bolaang Mongondow Selatan - Saputra, Ariandi (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This study aims to analyze the behavior of village officials in improving the quality of public services at the Momalia 1 Village Office, Posigadan District, South Bolaang Mongondow Regency. The method used is qualitative research method. Data collection techniques include observation and interviews and then analyzed to produce findings related to the behavior of village officials in providing services. The results showed that village officials in providing public services in Momalia 1 village, Posigadan sub-district, have shown an improvement in the quality of public services but have not run optimally. Providing information about the requirements that must be met by community members is not well conveyed so that people have to return home to complete the file. Knowledge in service by village officials is still lacking as there are unscrupulous employees who give priority to residents they know. conclusion that employee behavior in providing services at the Momalia 1 village office, Posigadan District, South Bolaang Mongondow Regency has shown towards improving the quality of public services, but not yet maximized. To improve the quality of public services, comprehensive efforts need to be made. Improvement measures should include educating the public about the existing public service system, as well as strict enforcement of rules and ethics for officers. In addition, it is also necessary to improve coordination between the government and the public.